ANTITUMORAL ANTIBACTERIAL AND ANTIFUNGAL ACTIVITIES OF KEFIR AND KEFIR GRAIN - (:unkn) unknown (JOHN WILEY & SONS LTD, 1994)
Kefir is a milk-derived product prepared by the incubation of kefir 'grains' with defatted milk. Various studies have been published on the therapeutic effects of kefir. However, few controlled studies and little information on the antibacterial, antifungal and antitumoural activities of kefir have been published. Therefore, these activities associated with kefir were investigated. The daily intraperitoneal administration of 0.50 mL kefir for 20 days to mice; containing transplanted fusiform cell carcomas resulted in a significant decrease in tumour size. Kefir-induced disappearance of tumoural necrosis was also evident. With respect to the antibacterial activity of kefir, the greatest activity was exhibited against gram-positive coccus, staphylococcus, and gram-positive bacillus. Kefir 'grains' showed higher antibacterial activity than kefir. Kefir also demonstrated antifungal activity against Candida, Saccharomyces, Rhodotorula, Torulopsis, Microsporum and Trichopyton species. The results demonstrate that kefir possesses antibacterial, antifungal and antineoplastic activities, and provides credence to the folklorec use of kefir for a variety of infectious and neoplastic diseases.
Keywords: KEFIR; KEFIR GRAINS; ANTINEOPLASTIC ACTIVITY; FUSIFORM CELL SARCOMAS; ANTIBACTERIAL ACTIVITY; ANTIFUNGAL ACTIVITY; POLYSACCHARIDE